Pengaruh Financial Stability, Ukuran Perusahaan, Kondisi Industri Terhadap Kecurangan Pelaporan Keuangan Pada Perusahaan yang Bergerak dibidang Keuangan yang Terdaftar di BEI Periode 2018-2019 - Hanik Riskiani; Yanto Yanto (Jurnal Rekognisi Akuntansi, 2020)
This study aims to test and determinine how much influence financial stability, size,nature of industry have on fraudulent financial reporting . This study uses three independent variables consisting of financial stability, size, and nature of industry and the dependent variable fraudulent financial reporting. This type of research is quantitave research. The population in this study are compines engaged in finance listed on the IDX for the 2018-2019 period with a purposive sampling method. The data analysis method used is multiple linear regression analysis with descriptive statistical test, classical assumption tests, and hypothesis testing winth the help of the SPSS 25. The result of this study indicate that financial stability ang nature of industry have significant negative effect on fraudulent financial reporting. Meanwhile, size has a significant positive effect on fraudulent financil reporting.